E-Sağlık Okuryazarlığı ve Çevrimiçi Sağlık Bilgisi Arama Davranışı Üzerine Bir Araştırma. - Gül, İsa; Demir, Sultan; Coşkun, İmran (Electronic Turkish Studies, 2022)
This study aimed to determine the e-health health levels of university students studying in the field of health sciences and to examine their online health information seeking behaviors. The research was planned in a descriptive and cross-sectional design. While the population of the research consists of 2012 students of Afyonkarahisar Health Sciences University Faculty of Health Sciences, 629 students form the sample. Questionnaire form was used as data collection tool in the research. The e-health literacy scale, which was adapted to Turkish, was used to measure e-health literacy. In order to determine the online health-seeking behaviors of the participants, categorical questions within the scope of the US National Cancer Institute Health Information National Trend Survey (HINTS) were used. The mean value of the e-health literacy scale in the study was found to be 3.74±0.67. In the study, a statistically significant difference was found between university students' grade level, continuous drug use and general health status variables and the mean scores of the e-health literacy scale. In online health seeking behaviors; 77.1% of them have Instagram, Facebook, Twitter etc. watched a video about health or illness with social media applications, 65.3% had any health)related software or application on their tablet or smartphone, 80.1% spent less than 1 hour searching for health information on the internet, 67%, It was determined that 8 of them moderately trust the information on health or medical issues on the internet and 58.6% find the internet useful when making decisions about their health. As a result, it has been determined that the e-health literacy level of university students in the field of health is sufficient, a significant majority of the students trust information about health and illness on the internet at a moderate level, and social media is an important source of information about health and illness.